Effects of combined biochemical inhibitors on nitrogen transformation and rice growth in paddy fields - YU Qiaogang; HUANG Zhengchen; YE Jing; SUN Wanchun; LIN Hui; WANG Qiang; WANG Feng; MA Junwei (浙江大学学报. 农业与生命科学版)
By selecting a typical blue clayey paddy soil with planting single-season rice in the southeast coast, we studied the effects of urea fertilizer containing N-(n-butyl) thiophosphoric triamide (NBPT, urease inhibitor) and 3, 4-dimethylpyrazole phosphate (DMPP, nitrification inhibitors) biochemical inhibitors on the nitrogen transformation in the surface water and soil and rice growth under the different fertilization times and levels. The results showed that: compared with the conventional urea fertilizer treatment, when the urea added with NBPT and DMPP combined biochemical inhibitors was applied twice as 50% base fertilizer and 50% topdressing, the concentrations of ammonium, nitrate and nitrite in field surface water decreased by 7.0% and 13.2%, 46.5% and 50.5%, 75.4% and 58.2% at the regreening stage and early tillering stage of rice, respectively; the ammonium concentration in soil decreased by 21.8% at the regreening stage and increased by 27.5% and 9.3% at the later tillering stage and jointing stage of rice; besides, the plant height, tiller number and chlorophyll content of rice were increased by 4.8% and 4.1%, 4.9% and 11.8%, 17.8% and 15.9% at the tillering stage and jointing stage, respectively. Furthermore, the yield and biomass of rice increased by 6.8% and 12.5%, 9.2% and 12.6%, respectively, at the mature stage, when the urea added with NBPT and DMPP combined biochemical inhibitors was applied once as base fertilizer or twice as 50% base fertilizer and 50% topdressing. In conclusion, the combined application of NBPT and DMPP biochemical inhibitors can effectively inhibit the rapid increase of ammonium and nitrate nitrogen in soil and field surface water, delay the transformation rate of nitrogen form, and maintain the relatively low nitrate nitrogen concentration in the surface water and soil in the rice fields, which can reduce the risk of nitrogen loss in paddy fields, promote rice growth and increase rice yield.